Masters of the English Reformation - Loane, Marcus Lawrence, 1911- (London, UK Hodder and Stoughton, 1983)
Includes bibliographical references and index.
First edition published 1954.
Keywords: Bilney, Thomas, -- c.1495-1531; Tyndale, William, -- c.1490-1536; Latimer, Hugh, -- c.1485-1555; Ridley, Nicholas, -- c.1500-1555; Cranmer, Thomas, -- 1489-1556; Reformation -- England -- Biography